Pengaruh Self Efficacy dan Motivasi Berprestasi terhadap Kemandirian Belajar pada Mahasiswa Prodi Kebidanan Diploma Tiga di Stikes Hamzar Lombok Timur - Siti Ramlan; Mukmin Suryatni; Baiq Handayani Rinuastuti (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
Independent learning is an activity based on the desire to use one's own ideas, solve problems, take risks and use various strategies to deal with situations, deal with problems that are relevant to one's own experience in learning activities. Factors that can affect independent learning are self-efficacy and achievement motivation. This study aims to determine the effect of self-efficacy and achievement motivation on the learning independence of DIII Midwifery Stikes Hamzar East Lombok students. The type of research used in this study is associative research, which aims to determine the relationship between two or more variables. The data collection method used in this study is a survey method. The population in this study were all DIII midwifery students at Stikes Hamzar, East Lombok, totaling 135 people. Data analysis was performed using multiple linear regression analysis. The results of the study at a significance level of 5% show that: (1) self-efficacy has a positive and significant effect on student learning independence (2) achievement motivation has a positive and significant effect on student learning independence.